An Overview on the potential application of ionic liquids in shale stabilization processes - Rahman, M.T. (Elsevier B.V., 2020)
This article comprehensively reviews the potential application and effects of different moieties of ionic liquids (ILs) on shale stabilization processes. The shale swelling inhibitory mechanisms and dispersion properties of 22 ILs were discussed. The effect of IL's concentration, temperature, chain length, cations, anions and polymerization functionally are discussed. Also, the toxicity and biodegradability of ILs are briefly provided. This study highlighted that more positive groups and alkyl substituents, and shorter alkyl chains are helpful for high performances. Understanding different IL's anion/cation effects are highly required. The study provides guidelines to design ILs for shale stabilization. Â© 2020 Elsevier B.V.